THE IMPACT OF COMMUNAL AND THRIFT SOCIETIES ON RURAL DEVELOPMENT: A STUDY OF BIAKWAN COMMUNITY, BOKI LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA - Takim Asu Ojua; Demsy Terwase Audu; Janet Punyit Plang; Edward D.I. Anzaku (European Scientific Journal, ESJ, 2013)
The study examines the role of communal contribution and thriftsocieties in the transformation of rural communities with reference toBiakwan community in Boki Local Government Area of Cross River StateNigeria. The study adopted the social survey method. Simple randomsampling was use in selecting the 251 respondents that participated in thestudy. Key Informant Interview (KII) was also held with women, men andyouth leaders within the community. The chi-square goodness-of-fit test wasused to test the hypothesis at 0.05 level of confidence. Findings showed asignificant relationship between participation in communal contribution andrural transformation. The recognition of already executed programmes andprojects by government and subsequent encouragement of communitymembers to continue with such transformative drive is recommended.